Penilaian Efisiensi Aplikasi MPDM Calculator Dalam Pengukuran Produktivitas Method Productivity Delay Model - Januardi, Redityo; Dewangga, Julian Pramudhita; Syaiful Aliim, Muhammad (Indonesian Society of Applied Science, 2025)
Technology can assist human needs in various sectors, including the construction sector. Its application has the opportunity to increase technical practicality, time, and cost efficiency, help speed up decision-making, and reduce the risk of errors. One challenge in construction implementation is the inadequate measurement of labor productivity and the lack of well-documented root causes, which can lead to delayed performance improvement decisions and incorrect conclusions. One effective method for productivity analysis is the MPDM (Method Productivity Delay Model), which can measure, predict, and improve productivity by identifying factors that cause delays. Currently, efforts have been made to digitalize part of the productivity measurement process of the MPDM method under the name MPDM Calculator Version 1.0. This application can be used for the data collection and processing stages of the MPDM method productivity calculation and is considered effective based on the same results as conventional methods. This study aims to determine and assess the efficiency of using the application in the process of calculating the productivity of the MPDM method. The results show that this application shortens the productivity measurement process significantly, where the test results for 2 case studies, obtained efficiency values of 153.2% and 156.1%. This application has the potential to be developed again in the process of analyzing productivity and recommending performance improvements to increase productivity. It is hoped that this application can answer the problem of using the MPDM method as one of the construction project control instruments.